THE EFFECT OF DIFFERENTIATED LEARNING ON STUDENTS NUMERACY LITERACY AT MIS NURUL ILMI IN BIMA CITY - Lulu Nadila Lestari; Agus Salam; Ade S. Anhar (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
One of the current issues in basic education is the low level of students' numeracy literacy, which also occurs in MIS Nurul Ilmi, Bima City. Students tend to be passive, less enthusiastic in monotonous learning, and show difficulty in understanding the basic concepts of reading and arithmetic. This problem is exacerbated by the lack of parental support in learning outside the classroom, which has an impact on their low literacy and numeracy skills. The purpose of this study was to determine the effect of differentiated learning on students' numeracy literacy. The research method used was quantitative with descriptive statistical research and the data analysis method used was simple linear regression analysis with the help of SPSS 16.0. The data presented in this study used primary data through questionnaires and student numeracy test results. The results showed that differentiated learning did not have a significant effect on students' numeracy literacy. This was indicated by the correlation coefficient value of 0.24 and the t-test result of 1.170, which was smaller than the t-table value of 1.734. The regression coefficient of 0.24 states that each increase in the differentiated learning variable (X) only contributes 24% to the increase in numeracy literacy (Y), while the remaining 76% is influenced by other factors outside this study.